Turning a spotlight on construction logistics for a sustainable urban environment—a review of current policy concepts and literature - Haag, Phillip; Jünger, Hans Christian (Frontiers in Built Environment, 2023)
Construction logistics is an influential participant in the overall urban freight network and a bottle neck for an efficient construction process. Especially in the urban area professionalization of its management may reduce negative impacts on the environment from which stakeholders, like construction companies, policy-makers and residents, do profit. In order to shed light on construction logistics in the urban environment in particular, a two-step methodological approach was pursued, which reconciles scientific findings with consideration in policies for the first time. Therefore, the current state of research was investigated by performing a systematic literature review and applying bibliometric keyword co-occurrence analyses in the first place. Moreover, policy papers (grey literature) on urban freight transportation of the 20 biggest cities in the DACH-region (Germany, Austria, Switzerland) were analyzed for their consideration of construction logistics in an initial case study. The results demonstrate limited consideration with only four cities paying deliberate attention within their overall logistics policy concepts and just one city providing construction logistics-specific policy recommendations. This is in line with the findings that although construction logistics in the urban environment is an emerging topic in academia, it is currently underrepresented in the context of urban logistics research. Therefore, combined results suggest insufficient translation of research findings into actionable policies despite existing literature providing possible ways to design future policies, e.g. by supporting decision-making. In conclusion, strategic management of construction logistics in the urban environment should be paid more attention to from both policy and academia in proportion to its environmental and socio-economic effects as well as its impact on the whole construction process. In that regard, predominately robust empirical data is needed in order to legitimate effective and sustainable concepts for urban construction logistics for both public and private actors.